Positive electrode active material for lithium ion secondary battery and lithium ion secondary battery

By using lithium composite oxide particles with a fine pore size of 0.0036 μm to 400 μm as the positive electrode active material of the lithium-ion secondary battery, the problem of insufficient charge and discharge capacity in the prior art was solved, and the charge and discharge characteristics of high capacity and high efficiency were achieved.

CN114424366BActive Publication Date: 2025-03-11SUMITOMO METAL MINING CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080064326.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-17
Filing Date
2020-09-16
Publication Date
2025-03-11
Estimated Expiration
2040-09-16

AI Technical Summary

Technical Problem

The charge and discharge capacity of the existing lithium-ion secondary batteries is insufficient, making it difficult to achieve a high-capacity positive electrode active material.

Method used

Lithium composite oxide particles with a fine pore size of 0.0036 μm to 400 μm were used as the positive electrode active material, and the average fine pore size was 0.2 μm to 1.0 μm to increase the contact area between the electrolyte and the positive electrode active material.

Benefits of technology

By increasing the contact area between the electrolyte solution and the positive electrode active substance, the charge and discharge capacity and charge and discharge efficiency of the lithium-ion secondary battery are enhanced, and the structure of the positive electrode active substance is stabilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005035144620000211
    Figure GDA0005035144620000211
  • Figure GDA0005035144620000221
    Figure GDA0005035144620000221
  • Figure GDA0005035144620000231
    Figure GDA0005035144620000231
Patent Text Reader

Abstract

The positive electrode active material for lithium ion secondary batteries according to the present invention has an average pore diameter of 0.2 μm to 1.0 μm when measured within a pore diameter range of 0.0036 μm to 400 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery and a lithium ion secondary battery. Background Art

[0002] In recent years, along with the popularization of portable electronic devices such as portable phones and notebook personal computers, it is strongly desired to develop a small and lightweight non-aqueous electrolyte secondary battery with high energy density. In addition, as the battery used for electric vehicles represented by hybrid vehicles, it is strongly desired to develop a secondary battery with excellent output characteristics and charge-discharge cycle characteristics.

[0003] As a secondary battery that meets these requirements, there is a lithium ion secondary battery. A lithium ion secondary battery is composed of a positive electrode, a negative electrode, an electrolyte solution, etc., and a material capable of lithium extraction and insertion is used as a positive electrode active material and a negative electrode active material.

[0004] Such lithium ion secondary batteries are currently being actively researched and developed. Among them, lithium ion secondary batteries using layered or spinel lithium composite oxides as positive electrode materials can achieve a high voltage of 4V and are therefore being put into practical use as batteries with high energy density.

[0005] As positive electrode materials for lithium-ion secondary batteries, lithium cobalt composite oxides (LiCoO2), lithium nickel composite oxides (LiNiO2), lithium nickel cobalt manganese composite oxides (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 O2), lithium excess nickel cobalt manganese composite oxide (Li2MnO3-LiNi x Mn y Co z O2) and other lithium composite oxides.

[0006] In the future, especially when used in electric vehicles and the like, there is a demand for further higher capacity of positive electrode materials in order to increase the cruising range.

[0007] As a method for increasing the capacity of positive electrode materials, controlling the structure of positive electrode materials has been studied. For example, Patent Document 1 discloses a non-aqueous electrolyte battery having both high discharge capacity and excellent cycle characteristics in a range of 0.001cc / g to 0.01cc / g of pore volume as a positive electrode active material.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2002-203552 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, during the charge and discharge reaction of a lithium ion secondary battery, lithium ions move between the positive electrode active material and the electrolyte. Therefore, in order to achieve the improvement of battery characteristics such as the high output of the lithium ion secondary battery, it is effective to use particles of a porous positive electrode active material with uniform pores on the surface to maximize the contact area between the positive electrode active material and the electrolyte.

[0013] However, the capacity of the obtained nonaqueous electrolyte battery is insufficient even when the positive electrode active material of Patent Document 1 is used. In order to further increase the capacity of lithium ion secondary batteries, a positive electrode active material that further increases the capacity of lithium ion secondary batteries is required.

[0014] Therefore, in view of the above-mentioned problems of the prior art, an object of one aspect of the present invention is to provide a positive electrode active material for lithium ion secondary batteries which can improve battery characteristics when used in lithium ion secondary batteries.

[0015] Methods for solving problems

[0016] In order to solve the above-mentioned problems, one embodiment of the positive electrode active material for lithium ion secondary batteries according to the present invention has an average pore diameter of 0.2 μm to 1.0 μm when the pore diameter is measured within a range of 0.0036 μm to 400 μm.

[0017] Effects of the Invention

[0018] When one embodiment of the positive electrode active material for lithium ion secondary batteries according to the present invention is used in lithium ion secondary batteries, battery characteristics can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is an explanatory diagram of the cross-sectional structure of the button-type battery produced in Example 1. DETAILED DESCRIPTION

[0020] Hereinafter, the embodiments of the present invention will be described in detail. In addition, the embodiments are not limited by the following description and can be appropriately changed within the scope of the gist of the present invention. In addition, in this specification, the wavy line "~" indicating the numerical range, unless otherwise specified, indicates that the numerical values ​​recorded before and after it are included as the lower limit and upper limit.

[0021] [Positive electrode active material for lithium ion secondary batteries]

[0022] The positive electrode active material for lithium ion secondary battery according to the present embodiment (hereinafter, also simply referred to as “positive electrode active material”) can include particles of lithium composite oxide.

[0023] The positive electrode active material according to the present embodiment has an average pore diameter of 0.2 to 1.0 μm, preferably 0.2 to 0.75 μm, more preferably 0.25 to 0.65 μm, and even more preferably 0.3 to 0.55 μm, when measured within a pore diameter range of 0.0036 to 400 μm.

[0024] In this embodiment, the pore diameter can be a value measured using a fully automatic pore diameter distribution measuring device (mercury porosimeter (PoreMaster 60-GT, manufactured by Quantachrome)). The average pore diameter is the average pore diameter of a plurality of pores, and the average value of the diameters of the individual pores can be used.

[0025] In general, when the positive electrode active material is used in a lithium ion secondary battery, the capacity of the positive electrode active material is affected by the contact area between the positive electrode active material and the electrolyte, so there is a tendency that the larger the specific surface area of ​​the positive electrode active material, the higher the capacity of the lithium ion secondary battery. However, sometimes even if the specific surface area of ​​the positive electrode active material increases, the capacity of the lithium ion secondary battery does not increase, but decreases. This is because the specific surface area of ​​the positive electrode active material is measured using a gas adsorption method that adsorbs gas in pores, so when the specific surface area of ​​the positive electrode active material is measured, the surface of the pores is also included in the measurement. However, it is believed that if the pore diameter of the pores is too small, the electrolyte does not enter the pores due to its surface tension, and the specific surface area of ​​the positive electrode active material is not effectively used.

[0026] Therefore, the positive electrode active material involved in this embodiment has an average pore diameter of 0.2 μm to 1.0 μm when the pore diameter is measured in the range of 0.0036 μm to 400 μm. If the average pore diameter when the pore diameter is measured in the range of 0.0036 μm to 400 μm is 0.2 μm or more, the electrolyte is easy to penetrate into the pores. Thus, the amount of pores that the electrolyte does not enter can be reduced, and the contact area with the electrolyte can be increased. Therefore, if the positive electrode active material is used for a lithium ion secondary battery, the charge and discharge capacity of the lithium ion secondary battery can be increased. On the other hand, if the average pore diameter when the pore diameter is measured in the range of 0.0036 μm to 400 μm is less than 1.0 μm, the strength of the positive electrode active material can be maintained. Therefore, by preventing the deformation of the positive electrode active material, the size of the pores can be reduced, and the size of the pores can be easily and stably maintained. Therefore, even when the positive electrode active material is used for a lithium ion secondary battery, it is easy to reduce a decrease in the charge and discharge capacity of the lithium ion secondary battery.

[0027] By making the positive electrode active material involved in this embodiment have an average pore size of 0.2 μm to 1.0 μm when measured in the range of pore size of 0.0036 μm to 400 μm, it is possible to have multiple uniform pores on the surface and inside of the particle. Therefore, when the positive electrode active material involved in this embodiment is used as the positive electrode of a lithium ion secondary battery, the battery characteristics of the lithium ion secondary battery such as charging capacity, discharge capacity and charge and discharge efficiency can be improved.

[0028] In addition, in the present embodiment, as in the following formula (1), the ratio S2 / S1 of the cumulative specific surface area S2 measured in the range of pore diameter 0.0036μm to 0.5μm relative to the cumulative specific surface area S1 measured in the range of 0.0036μm to 400μm is set as the ratio of fine pores. At this time, the ratio of fine pores of the positive electrode active material involved in the present embodiment is preferably 70% to 92%, more preferably 80% to 90%, and further preferably 83% to 88%. The positive electrode active material involved in the present embodiment is adjusted in a manner that the cumulative specific surface area S2 does not become relatively too high relative to the cumulative specific surface area S1 by making the ratio of fine pores 70% to 92%. Thus, the pores that are not effectively used when measuring battery characteristics can be reduced, and thus the battery characteristics of the lithium ion secondary battery can be further improved by using the positive electrode active material involved in the present embodiment as the positive electrode of the lithium ion secondary battery. In addition, the cumulative specific surface area can be measured, for example, using a flow-type gas adsorption method specific surface area measuring device or the like.

[0029] Micropore ratio (%) = (cumulative specific surface area S2 measured in the range of pore diameter 0.0036 μm to 0.5 μm) / (cumulative specific surface area S1 measured in the range of 0.0036 μm to 400 μm) × 100 (1)

[0030] The composition of the lithium composite oxide is not limited, and examples thereof include lithium nickel composite oxides. For example, the lithium nickel composite oxide can contain lithium (Li), nickel (Ni), cobalt (Co), and an element (also referred to as an additive element) M (M) in a ratio of Li:Ni:Co:M=1+a:1-xy:x:y in terms of the amount of matter. However, a, x, and y in the above formula preferably satisfy -0.05≤a≤0.50, 0≤x≤0.35, and 0≤y≤0.35, respectively. In addition, the element M can be at least one element selected from Mg, Ca, Al, Si, Fe, Cr, Mn, V, Mo, W, Nb, Ti, Zr, and Ta.

[0031] For example, lithium nickel composite oxide can be composed of the general formula Li 1+a Ni 1-x-y Cox M y O 2+α In the above general formula, a, x and y have been described above, so the description is omitted here. In addition, α is preferably, for example, 0≤α≤0.10.

[0032] [Method for producing positive electrode active material for lithium ion secondary battery]

[0033] The method for producing the positive electrode active material according to the present embodiment is described. The method for producing the positive electrode active material according to the present embodiment may include a crystallization step, a mixing step, and a calcination step. The method for producing the positive electrode active material according to the present embodiment may include an oxidative roasting step between the crystallization step and the mixing step as needed, and the oxide obtained by the oxidative roasting step may be used in the mixing step.

[0034] (A) Crystallization process

[0035] Nickel composite hydroxide particles containing nickel and an additive element M (nickel composite hydroxide particles) are crystallized by a crystallization method (crystallization step).

[0036] For example, nickel composite hydroxide can be represented by the general formula: Ni 1-x-y Co x M y (OH) 2+β In the above formula, x and y preferably satisfy the above-described ranges. β is preferably -0.2≤β≤0.2, for example.

[0037] The specific steps of the crystallization process are not particularly limited. For example, a mixed aqueous solution containing nickel (Ni) and an additive element M can be mixed with an alkaline aqueous solution to crystallize the particles of the nickel composite hydroxide. Specifically, for example, it is preferably implemented by the following steps. In addition, the mixed aqueous solution can further contain cobalt (Co).

[0038] First, water is added to the reaction tank and controlled to a predetermined atmosphere and temperature. In addition, the atmosphere in the reaction tank during the crystallization step is not particularly limited, and can be set to an inert gas atmosphere such as a nitrogen atmosphere. In addition, in addition to the inert gas, a gas containing oxygen such as air can be combined and supplied to adjust the dissolved oxygen concentration of the solution in the reaction tank. In addition to water, an alkaline aqueous solution or a complex described later can be further added to the reaction tank to prepare an initial aqueous solution.

[0039] Then, a mixed aqueous solution containing at least nickel and an additive element M and an alkaline aqueous solution are added to the reaction tank to prepare a reaction aqueous solution. Next, the reaction aqueous solution is stirred at a constant speed and the pH is controlled so that particles of the nickel composite hydroxide can be coprecipitated and crystallized in the reaction tank.

[0040] In addition, instead of supplying the mixed aqueous solution containing nickel and the additive element M to the reaction tank, a mixed aqueous solution containing a part of the metal and an aqueous solution containing the remaining metal may be supplied to the reaction tank. Specifically, for example, a mixed aqueous solution containing nickel and an aqueous solution containing the additive element M may be supplied. In addition, aqueous solutions of each metal may be prepared separately and the aqueous solutions containing each metal may be supplied to the reaction tank.

[0041] The mixed aqueous solution containing nickel and the additive element M can be prepared by adding salts of each metal to water as a solvent. The type of salt is not particularly limited. For example, as a salt of nickel, one or more salts selected from sulfates, nitrates, and chlorides can be used. In the case of containing cobalt, one or more salts selected from sulfates, nitrates, and chlorides can be used as a salt of cobalt. In addition, the types of the salts of each metal may be different, but from the viewpoint of preventing the mixing of impurities, salts of the same type are preferably used.

[0042] As the salt containing the additive element M, for example, one or more selected from manganese sulfate, manganese chloride, titanium sulfate, tungsten oxide, molybdenum oxide, molybdenum sulfide, vanadium pentoxide, calcium chloride, aluminum sulfate, sodium aluminate, magnesium sulfate, magnesium chloride, magnesium carbonate, etc. can be used.

[0043] The alkaline aqueous solution can be prepared by adding an alkaline component to water as a solvent. The type of the alkaline component is not particularly limited, and for example, one or more selected from sodium hydroxide, potassium hydroxide, sodium carbonate, etc. can be used.

[0044] The composition of the metal elements contained in the mixed aqueous solution is substantially the same as the composition of the metal elements contained in the obtained nickel composite hydroxide. Therefore, it is preferable to adjust the composition of the metal elements of the mixed aqueous solution to be the same as the composition of the metal elements of the target nickel composite hydroxide.

[0045] In the crystallization step, in addition to the aqueous solution (mixed aqueous solution) containing the above-mentioned metal component and the alkaline aqueous solution, an arbitrary component can be added to the reaction aqueous solution.

[0046] For example, the complex can also be added to the aqueous reaction solution together with the alkaline aqueous solution.

[0047] The complex is not particularly limited, as long as it is a complex that can form a coordination compound by combining with nickel ions or other metal ions in an aqueous solution. As the complex, for example, an ammonium ion donor can be cited. As the ammonium ion donor, it is not particularly limited, for example, one or more selected from ammonia, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc. can be used.

[0048] The temperature of the reaction aqueous solution in the crystallization step is not particularly limited. For example, when no complex is used, the temperature of the mixed aqueous solution is preferably in the range of more than 60° C. and 80° C. or less.

[0049] When no complex is used in the crystallization step, the solubility of Ni increases by increasing the temperature of the reaction aqueous solution to more than 60° C., so that the amount of Ni precipitation deviates from the target composition, and the phenomenon of no coprecipitation can be more reliably avoided.

[0050] In addition, by keeping the temperature of the reaction aqueous solution in the crystallization step below 80°C, the evaporation of water can be suppressed, thereby preventing the slurry concentration from increasing. By preventing the slurry concentration from increasing, for example, unintended crystal precipitation of sodium sulfate or the like in the reaction aqueous solution can be suppressed, which can prevent the impurity concentration from increasing.

[0051] The pH of the mixed aqueous solution in the crystallization step can be appropriately adjusted according to the particle size of the nickel composite hydroxide, for example, when no complex is used, the pH of the reaction aqueous solution is preferably 10 to 12. In addition, the pH of the reaction aqueous solution in this specification refers to the pH at the temperature of the reaction aqueous solution unless otherwise specified.

[0052] In the crystallization step, when a complex is not used, by setting the pH of the reaction aqueous solution to 12 or less, it is possible to prevent the nickel composite hydroxide particles from becoming fine particles, thereby improving filterability and more reliably obtaining spherical particles.

[0053] By setting the pH of the reaction aqueous solution to 10 or more, the generation rate of nickel composite hydroxide particles can be accelerated, and for example, some components such as Ni can be prevented from remaining in the filtrate. Therefore, nickel composite hydroxide particles of the target composition can be obtained more reliably.

[0054] On the other hand, in the crystallization step, when an ammonium ion donor such as ammonia is used as a complex, the solubility of Ni increases, and thus the pH of the reaction aqueous solution in the crystallization step is preferably 10 to 13.5. In this case, the temperature of the reaction aqueous solution is preferably 30°C to 60°C.

[0055] When the reaction aqueous solution does not use an ammonium ion donor as a complex, the ammonia concentration in the reaction aqueous solution is preferably maintained within a constant range of 3 g / L to 25 g / L in the reaction tank.

[0056] By setting the ammonia concentration in the reaction aqueous solution to 3 g / L or more, the solubility of metal ions can be kept constant, thereby forming primary particles of nickel composite hydroxide having uniform shape and particle size. Therefore, the expansion of the particle size distribution of the obtained nickel composite hydroxide particles can be suppressed.

[0057] Furthermore, by setting the ammonia concentration in the reaction aqueous solution to 25 g / L or less, the solubility of metal ions can be prevented from excessively increasing, and the amount of metal ions remaining in the reaction aqueous solution can be suppressed, thereby more reliably obtaining nickel composite hydroxide particles of the desired composition.

[0058] In addition, if the ammonia concentration changes, the solubility of the metal ions changes, and sometimes uniform hydroxide particles are not formed, so it is preferably kept within a certain range. For example, during the crystallization step, the ammonia concentration is preferably kept within a desired concentration with the upper and lower limits within about 5 g / L.

[0059] After the stable state is reached, the precipitate is collected, filtered and washed with water to obtain nickel composite hydroxide particles. Alternatively, the mixed aqueous solution and the alkaline aqueous solution, and depending on the situation, an aqueous solution further containing an ammonium ion donor, can be continuously supplied to the reaction tank, so that the precipitate overflows from the reaction tank, is collected, filtered, and washed with water to obtain nickel composite hydroxide particles.

[0060] In addition, the additive element M optimizes the crystallization conditions and makes it easier to control the composition ratio, so it can also be added by coating the surface of the particles of the nickel composite hydroxide with the additive element M. In this case, the crystallization step can further include a coating step of coating the surface of the obtained nickel composite hydroxide particles with the additive element M.

[0061] (Coating process)

[0062] In the coating step, the method for coating the surface of the nickel composite hydroxide particles with the additional element M is not particularly limited, and various known methods can be used.

[0063] For example, the particles of nickel composite hydroxide are dispersed in pure water to form a slurry. A solution of the added element M containing the target coating amount is mixed in the slurry, and an acid is added dropwise in a manner to form a predetermined pH to adjust the pH value. The acid at this time is not particularly limited, and preferably one or more selected from, for example, sulfuric acid, hydrochloric acid, nitric acid, etc. is used.

[0064] After the pH of the mixed solution containing the slurry and the additive element M is adjusted, the mixed solution is mixed for a predetermined time, and then filtered and dried to obtain a nickel composite hydroxide coated with the additive element M.

[0065] The method of coating the surface of the particles of the nickel composite hydroxide with the additive element M is not limited to the above method. For example, a method of drying a solution of a compound containing the additive element M and a solution containing particles of the nickel composite hydroxide by spray drying, a method of impregnating particles of the nickel composite hydroxide with a solution of a compound containing the additive element M, etc. can also be used.

[0066] In addition, the particles of the nickel composite hydroxide provided in the coating step may be particles to which a part of the additive element M is added in advance, or may be particles not containing the additive element M. In the case where a part of the additive element M is added in advance, as described above, an aqueous solution containing the additive element M can be added to the mixed aqueous solution during, for example, crystallization. In this way, when the particles of the nickel composite hydroxide contain a part of the additive element M, it is preferred to adjust the amount of the additive element M added in the coating step so as to obtain the target composition.

[0067] In the crystallization process, a preliminary test can be performed in advance to calculate the relationship between the crystallization conditions such as the pH or ammonia concentration of the reaction aqueous solution and the pore size of the positive electrode active material involved in the present embodiment, and the crystallization conditions in the crystallization process are prepared to make the pore size of the positive electrode active material involved in the present embodiment 0.0036μm~400μm. The crystallization process is preferably based on the results of the preliminary test prepared in advance, so that the pore size of the positive electrode active material involved in the present embodiment becomes 0.0036μm~400μm, and the crystallization conditions are selected to perform.

[0068] (B) Oxidation roasting process

[0069] The nickel composite hydroxide obtained in the crystallization step is calcined (oxidative calcination) in an atmosphere containing oxygen and then cooled to room temperature, thereby obtaining a nickel composite oxide (nickel composite calcined product).

[0070] For example, nickel composite oxide can be represented by the general formula: Ni 1-x-y Co x M y O 1+γ In the above formula, x and y preferably satisfy the above-described ranges. For example, γ is preferably -0.2≤γ≤0.2.

[0071] In addition, in the oxidation roasting process, the nickel composite hydroxide is calcined to reduce the water content, so that at least a part of it becomes a nickel composite oxide as described above. However, in the oxidation roasting process, it is not necessary to completely convert the nickel composite hydroxide into a nickel composite oxide, and the so-called nickel composite oxide here, for example, can contain nickel composite hydroxide and its intermediates.

[0072] The calcination conditions in the oxidation calcination step are not particularly limited, but it is preferably calcined in an atmosphere containing oxygen, such as an air atmosphere, at a temperature of 350° C. to 1000° C. for 5 to 24 hours.

[0073] This is because the specific surface area of ​​the obtained nickel composite oxide can be prevented from being excessively increased by setting the calcination temperature to 350° C. or higher, and because the specific surface area of ​​the nickel composite oxide can be prevented from being excessively reduced by setting the calcination temperature to 1000° C. or lower.

[0074] This is because by making the firing time be more than 5 hours, thereby can make the temperature in the firing container even especially, can evenly react.In addition, even compared with 24 hours, carry out long-time firing, the nickel composite oxide obtained does not observe big change yet, therefore consider from the viewpoint of energy efficiency, the firing time is preferably below 24 hours.

[0075] The oxygen concentration in the oxygen-containing atmosphere during heat treatment is not particularly limited, and for example, the oxygen concentration is preferably 20% by volume or more. Since it can also be an oxygen atmosphere, the upper limit of the oxygen concentration of the oxygen-containing atmosphere can be 100% by volume.

[0076] (C) Mixing process

[0077] In the mixing step, the nickel composite compound and the lithium compound can be mixed to obtain a raw material mixture (also referred to as a lithium composite oxide precursor).

[0078] The nickel composite compound may be a nickel composite hydroxide obtained in the crystallization step, or a nickel composite calcined product obtained in the oxidative calcination step, or a mixture thereof. The nickel composite compound preferably has a composition corresponding to the target lithium composite oxide.

[0079] For example, in the case of obtaining a lithium composite oxide having the above composition ratio, the nickel composite compound can contain nickel (Ni), cobalt (Co) and element M (M) in a ratio of Ni:Co:M=1-xy:x:y in terms of the amount of matter. However, x and y in the above formula preferably satisfy the ranges already described. In addition, the element M can use the same element as described above.

[0080] In addition, the mixing ratio of the lithium compound and the nickel composite compound is not particularly limited. However, before and after the lithium composite oxide precursor is calcined, the ratio (Li / Me) of the number of atoms of lithium (Li) and the number of atoms of metals other than lithium (Me) in the lithium composite oxide precursor is almost unchanged. Therefore, the Li / Me in the lithium composite oxide precursor is almost the same as the Li / Me in the obtained lithium composite oxide. Thus, it is preferred to mix the Li / Me in the lithium composite oxide precursor in the same manner as the Li / Me in the lithium composite oxide to be obtained. In addition, Li / Me refers to the ratio of the number of atoms of lithium and metals other than lithium contained in the lithium composite oxide precursor.

[0081] For example, it is preferable to mix the lithium composite oxide so that Li / Me is 0.95 to 1.5. In particular, it is more preferable to mix the lithium composite oxide precursor so that Li / Me is 1.0 to 1.2.

[0082] As the lithium compound, for example, one or more selected from lithium carbonate, lithium hydroxide, etc. can be used. In addition, lithium hydroxide sometimes has hydration water, and can also be used in a state with hydration water, preferably pre-baked to reduce hydration water. It is particularly preferred to use anhydrous lithium hydroxide that has been anhydrous.

[0083] It is preferred that the particle sizes of the nickel composite compound and the lithium compound be adjusted in advance so as to obtain a desired lithium composite oxide after the calcining step.

[0084] The nickel composite compound and the lithium compound can be mixed using a general mixer, for example, one or more selected from a vibration mixer, a Lödige mixer, a Julia mixer, a V-type blender, etc. The mixing conditions in the mixing step are not particularly limited, but the conditions are preferably selected in such a manner that the components of the raw materials are fully mixed without destroying the structure of the particles of the raw materials such as the nickel composite oxide.

[0085] The lithium composite oxide precursor is preferably fully mixed in a mixing step before being subjected to the calcining step. If the mixing is insufficient, there is a possibility that the Li / Me ratio varies between particles, and sufficient battery characteristics cannot be obtained.

[0086] The nickel composite compound and the lithium compound are preferably weighed and mixed in a manner that lithium (Li), nickel (Ni), cobalt (Co) and the additive element M (M) are contained in a ratio of Li:Ni:Co:Zr:M=1+a:1-xy:x:y in terms of the mass ratio of the mixed lithium composite oxide precursor. The suitable ranges of a, x and y in such a formula can be the same as those described above, and thus the description thereof is omitted here.

[0087] This is because the content ratio of each metal hardly changes before and after the sintering process, so it is preferred to mix the lithium composite oxide precursor in such a way that the content ratio of each metal becomes the same as the target content ratio of each metal of the positive electrode active material obtained by the method for producing the positive electrode active material involved in this embodiment.

[0088] (D) Firing process

[0089] The lithium composite oxide precursor obtained in the mixing step is calcined at 600° C. to 1050° C. in an oxygen-containing atmosphere having an oxygen concentration of 80% to 97% by volume (calcination step). Thus, the positive electrode active material according to the present embodiment can be obtained as a particulate lithium composite oxide.

[0090] The amount of the lithium composite oxide precursor filled in the calcining container is not particularly limited and can be appropriately adjusted depending on the size of the calcining container and the like.

[0091] When the calcining container is filled with the lithium composite oxide precursor, the shape of the lithium composite oxide precursor is not particularly limited, and the shape and the like can be selected so that it can be heated uniformly in the calcining step.

[0092] The calcination temperature for calcining the lithium composite oxide precursor is not particularly limited and can be appropriately set according to the composition of the lithium composite oxide precursor.

[0093] By setting the calcination temperature to 600° C. or higher, the lithium component can be fully diffused into the metal composite compound such as the nickel composite oxide, and the characteristics of the obtained lithium composite oxide can be made particularly uniform. Thus, when the obtained lithium composite oxide is used as a positive electrode active material, the battery characteristics can be particularly improved. In addition, the reaction can be fully carried out, so the residual lithium and the residual unreacted particles can be suppressed.

[0094] By setting the calcination temperature to 1050° C. or lower, sintering between particles of the generated lithium composite oxide can be suppressed. Also, by setting the calcination temperature to 1050° C. or lower, abnormal grain growth can be suppressed, and coarsening of the particles of the obtained lithium composite oxide can be suppressed.

[0095] In the process of raising the temperature to the heat treatment temperature, it is preferred to maintain the temperature near the melting point of the lithium compound for about 1 to 5 hours because the reaction can proceed more uniformly.

[0096] In the calcination process, the holding time at the predetermined temperature, i.e., the above-mentioned calcination temperature, is not particularly limited, and is preferably 2 hours or more, and more preferably 3 hours or more. By making the holding time at the calcination temperature be 2 hours or more, the generation of the lithium composite oxide can be fully promoted, and the residue of the unreacted product can be more reliably prevented.

[0097] The upper limit of the holding time at the calcination temperature is not particularly limited, but is preferably 24 hours or less in consideration of productivity and the like.

[0098] The atmosphere during firing is not particularly limited, but is preferably an oxidizing atmosphere. As the oxidizing atmosphere, a gas atmosphere containing oxygen can be preferably used, and for example, an atmosphere having an oxygen concentration of 18 vol% to 100 vol% is more preferably used.

[0099] This is because the crystallinity of the lithium composite oxide can be particularly improved by setting the oxygen concentration in the atmosphere during firing to 18 vol % or more.

[0100] In the case of a gas atmosphere containing oxygen, as the gas constituting the atmosphere, for example, air (atmosphere), oxygen, a mixed gas of oxygen and an inert gas, etc. can be used. In addition, as the gas constituting the gas atmosphere containing oxygen, for example, as described above, when a mixed gas of oxygen and an inert gas is used, the oxygen concentration in the mixed gas preferably satisfies the above range. In particular, in the firing process, it is preferably implemented in a gas flow of a gas containing oxygen, and more preferably in air or an oxygen flow. In particular, if battery characteristics are considered, it is preferably carried out in an oxygen flow.

[0101] The furnace used for sintering is not particularly limited. For example, a furnace that can sinter the precursor filling for lithium composite oxide production in air or oxygen flow can be suitably used. From the perspective of maintaining a uniform atmosphere in the furnace, an electric furnace that does not generate gas is preferably used. Both intermittent and continuous furnaces can be used.

[0102] (Preliminary Firing Process)

[0103] In addition, in the present embodiment, the raw material mixture (lithium composite oxide precursor) obtained in the mixing step may be temporarily calcined before the calcining step. When the temporary calcination is performed, the temporary calcination temperature is not particularly limited, and can be a temperature lower than the calcination temperature in the calcining step. The temporary calcination temperature is, for example, preferably 250°C to 700°C, and more preferably 350°C to 650°C.

[0104] The calcination time, that is, the holding time at the calcination temperature is, for example, preferably about 1 to 10 hours, more preferably 3 to 6 hours.

[0105] The firing step may be performed after temporary firing and temporary cooling, or the firing step may be performed continuously by raising the temperature from the temporary firing temperature to the firing temperature.

[0106] The atmosphere during the pre-firing is not particularly limited, and for example, the same atmosphere as that in the firing step can be used.

[0107] By performing the calcination, lithium is sufficiently diffused into the metal composite compound such as the nickel composite oxide, and a particularly uniform lithium composite oxide can be obtained.

[0108] [Lithium-ion secondary battery]

[0109] Next, a lithium ion secondary battery (hereinafter also referred to as a "secondary battery") to which the positive electrode active material according to the present embodiment is applied will be described. The secondary battery according to the present embodiment has a positive electrode using the above-described positive electrode active material as a positive electrode material.

[0110] The secondary battery involved in this embodiment includes, for example, a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte, and is composed of the same components as a general lithium-ion secondary battery. In addition, the embodiments described below are merely illustrative, and the secondary battery involved in this embodiment is represented by the following embodiments, and can be implemented in various modified and improved forms based on the knowledge of those skilled in the art. In addition, the use of the secondary battery is not particularly limited. Below, for the secondary battery involved in this embodiment, each component is described separately.

[0111] (positive electrode)

[0112] The positive electrode included in the secondary battery according to this embodiment can contain the above-mentioned positive electrode active material.

[0113] An example of a method for manufacturing a positive electrode is described. First, a positive electrode active material (powder), a conductive material, and a binder (adhesive) are mixed to form a positive electrode composite material, and activated carbon, a solvent for viscosity adjustment, and the like are further added as needed, and the mixture is kneaded to form a positive electrode composite material paste.

[0114] The mixing ratio of each material in the positive electrode composite material becomes a factor that determines the performance of the lithium secondary battery, so it can be adjusted according to the purpose. The mixing ratio of the materials can be the same as that of the positive electrode of the known lithium secondary battery. For example, when the total mass of the solid component of the positive electrode composite material excluding the solvent is 100 mass%, the positive electrode active material can be contained in a ratio of 60 mass% to 95 mass%, the conductive material in a ratio of 1 mass% to 20 mass%, and the adhesive in a ratio of 1 mass% to 20 mass%.

[0115] The obtained positive electrode composite material paste is applied to the surface of a current collector made of aluminum foil, for example, and dried to disperse the solvent to produce a sheet-like positive electrode. As required, there is also a roller pressing method to increase the electrode density. The sheet-like positive electrode obtained by this operation can be cut into an appropriate size according to the target battery, etc., for the production of the battery.

[0116] As the conductive material, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.), acetylene black, Ketjen Black (registered trademark), or other carbon black-based materials can be used.

[0117] As the binder (adhesive), it is possible to use a binder that plays a role in connecting active material particles, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin, polyacrylic acid, etc. can be used.

[0118] As required, the positive electrode active material, the conductive material and the activated carbon are dispersed, and the solvent for dissolving the binder is added to the positive electrode composite material. As the solvent, specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used. In addition, the positive electrode composite material can also be added with activated carbon in order to increase the double electric layer capacity.

[0119] The method for producing the positive electrode is not limited to the above-mentioned method, and other methods may be used. For example, the positive electrode composite material may be pressed into shape and then dried in a vacuum atmosphere.

[0120] (negative electrode)

[0121] The negative electrode can use metallic lithium, lithium alloy, etc. In addition, the negative electrode can be a negative electrode active material that can absorb and release lithium ions, mixed with a binder, and a negative electrode composite material made into a paste by adding a suitable solvent is applied to the surface of a metal foil collector such as copper, dried, and compressed to increase the electrode density as needed.

[0122] As the negative electrode active material, for example, natural graphite, artificial graphite, sintered organic compounds such as phenolic resin, powders of carbon materials such as coke can be used. In this case, as the negative electrode binder, similar to the positive electrode, fluorine-containing resins such as PVDF can be used, and as the solvent for dispersing these active materials and the binder, organic solvents such as N-methyl-2-pyrrolidone can be used.

[0123] (Diaphragm)

[0124] The positive electrode and the negative electrode may be arranged with a separator interposed therebetween as required. The separator separates the positive electrode and the negative electrode and retains the electrolyte, and a known separator may be used, for example, a thin film such as polyethylene or polypropylene having a large number of minute pores may be used.

[0125] (Non-aqueous electrolyte)

[0126] As the non-aqueous electrolyte, for example, a non-aqueous electrolyte solution can be used. As the non-aqueous electrolyte solution, for example, a non-aqueous electrolyte solution in which a lithium salt as a supporting salt is dissolved in an organic solvent can be used. In addition, as the non-aqueous electrolyte solution, a non-aqueous electrolyte solution in which a lithium salt is dissolved in an ionic liquid can be used. In addition, the so-called ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is liquid even at room temperature.

[0127] As the organic solvent, one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc. can be used alone, and two or more thereof can also be mixed and used.

[0128] As the supporting salt, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2 and complex salts thereof can be used. Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant and the like.

[0129] In addition, as the non-aqueous electrolyte, a solid electrolyte can be used. The solid electrolyte has the property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.

[0130] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.

[0131] The oxide-based solid electrolyte is not particularly limited, and can be suitably used, for example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation. As the oxide-based solid electrolyte, for example, lithium phosphate (Li3PO4), Li3PO4N X 、LiBO2N X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≤X≤1), Li 1+X Al X Ge 2-X (PO4)3(0≤X≤1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≤X≤2 / 3), Li5La3Ta2O 12 、Li7La3Zr2O 12 、Li6BaLa2Ta2O 12 , Li 3.6 Si 0.6 P 0.4 One or more of O4, etc.

[0132] As the sulfide-based solid electrolyte, there is no particular limitation, and for example, a sulfide-based solid electrolyte containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. As the sulfide-based solid electrolyte, for example, one or more selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc. can be used.

[0133] In addition, as the inorganic solid electrolyte, an inorganic solid electrolyte other than those described above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.

[0134] The organic solid electrolyte is not particularly limited as long as it is a polymer compound showing ion conductivity, and for example, polyethylene oxide, polypropylene oxide, and copolymers thereof can be used. In addition, the organic solid electrolyte may contain a supporting salt (lithium salt).

[0135] (Shape and structure of secondary battery)

[0136] As described above, the lithium-ion secondary battery involved in the present embodiment can adopt various shapes such as cylindrical and stacked shapes. Even in the case of adopting any shape, if the secondary battery involved in the present embodiment uses a non-aqueous electrolyte as a non-aqueous electrolyte, the positive electrode and the negative electrode can be stacked across a separator to form an electrode body. The non-aqueous electrolyte is impregnated in the obtained electrode body, and the positive electrode collector is connected to the positive terminal connected to the outside and the negative electrode collector is connected to the negative terminal connected to the outside using a collector lead, etc., to form a structure sealed in the battery case.

[0137] In addition, in the present embodiment, the secondary battery involved in the present embodiment is not limited to the method of using a non-aqueous electrolyte as a non-aqueous electrolyte, for example, a secondary battery using a solid non-aqueous electrolyte, i.e., an all-solid battery, can also be used. In the case of an all-solid battery, the composition other than the positive electrode active material can be appropriately changed as needed.

[0138] Example

[0139] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the present invention is not limited to the following Examples.

[0140] Hereinafter, the positive electrode active material and the method for producing and evaluating the secondary battery used in each of the Examples and Comparative Examples will be described.

[0141] <Example 1>

[0142] [Production of positive electrode active material and secondary battery]

[0143] (1) Preparation of nickel composite oxide

[0144] (Crystallization process)

[0145] First, the crystallization conditions (pH or ammonia concentration of the reaction aqueous solution, etc.) in the crystallization process are confirmed by preliminary tests to make the pore diameter of the positive electrode active material 0.2 μm to 1.0 μm when the average pore diameter is measured within the range of 0.0036 μm to 400 μm. The crystallization conditions are selected so that the average pore diameter is 0.530 μm when measured within the range of 0.0036 μm to 400 μm, and the nickel composite hydroxide particles with a material ratio of nickel: cobalt: aluminum of Ni: Co: Al = 92: 5: 3 are crystallized.

[0146] Then, the slurry containing the recovered nickel composite hydroxide particles is filtered, and water-soluble impurities are washed away with ion-exchanged water, followed by drying.

[0147] The particle size distribution of the obtained nickel composite hydroxide particles was measured using a laser diffraction scattering particle size distribution measuring apparatus (MICROTRAC HRA, manufactured by Nikkiso Co., Ltd.). The average particle size of the nickel composite hydroxide particles was denoted by the median particle size D. 50 It is calculated to be 14.3 μm.

[0148] (Oxidation roasting process)

[0149] Next, the obtained nickel composite hydroxide particles were oxidatively calcined at 500° C. for 5 hours in an air flow (oxygen concentration: 21 volume %). Thus, a nickel-cobalt composite oxide (Ni 200 Å) in which nickel:cobalt:aluminum was solid-dissolved in a molar ratio of 92:5:3 was obtained. 0.92 Co 0.05 Al 0.03 O) particles (nickel-cobalt composite oxide particles).

[0150] (2) Manufacturing of positive electrode active material

[0151] (Mixing process)

[0152] The obtained nickel-cobalt composite oxide particles and lithium hydroxide as a lithium compound were fully mixed using a vibration mixer device (Willie et Bakkofen (WAB) model: TURBULA Type T2C) to prepare a raw material mixture (lithium composite oxide precursor). At this time, each raw material was weighed and mixed so that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium contained in the obtained lithium composite oxide precursor, i.e., Li / Me, was 1.05.

[0153] (Firing process)

[0154] The lithium composite oxide precursor obtained in the mixing step was calcined at 790° C. for 10 hours in an oxygen-containing atmosphere with an oxygen concentration of 90% by volume and the remainder being nitrogen. The calcined product was pulverized with a pin mill at a strength sufficient to maintain the particle shape.

[0155] Through the above steps, porous lithium composite oxide particles (lithium composite oxide powder) were obtained.

[0156] (Washing and drying process)

[0157] Water was mixed in a ratio of 150 parts by mass with respect to 100 parts by mass of the obtained lithium composite oxide particles, and after stirring with water, suction was performed using a suction filter to obtain a precipitate (water washing step). The obtained precipitate was placed in a SUS container, heated to 100° C. using a vacuum dryer, then heated at 190° C. for 12 hours, and further left to dry for 10 hours to obtain a positive electrode active material (drying step).

[0158] The composition and phase heterogeneity of the obtained positive electrode active material were confirmed. As a result, it was confirmed that the positive electrode active material obtained by this experimental example was composed of the general formula: Li 0.98 Ni 0.92 Co 0.05 Al 0.03 The lithium composite oxide shown in FIG. 2 was formed. No heterogeneous phase was confirmed from the XRD pattern of the active material. In addition, the BET specific surface area of ​​the positive electrode active material was 1.2 m 2 / g.

[0159] (3) Production of secondary batteries

[0160] Follow these steps to make Figure 1 The button-type battery of the structure shown in FIG. Figure 1 As shown, the button-type battery 10 is composed of a case 11 and an electrode 12 accommodated in the case 11 .

[0161] The shell 11 has a positive electrode can 111 which is hollow and opened at one end, and a negative electrode can 112 arranged at the opening of the positive electrode can 111. If the negative electrode can 112 is arranged at the opening of the positive electrode can 111, a space for accommodating the electrode 12 is formed between the negative electrode can 112 and the positive electrode can 111.

[0162] The electrode 12 is formed of a positive electrode 121 , a separator 122 , and a negative electrode 123 , which are stacked in this order and housed in the case 11 such that the positive electrode 121 contacts the inner surface of the positive electrode can 111 , and the negative electrode 123 contacts the inner surface of the negative electrode can 112 .

[0163] The housing 11 is provided with a gasket 113, and the positive electrode can 111 and the negative electrode can 112 are fixed by restricting relative movement so as to maintain a non-contact state, that is, an electrically insulated state. The gasket 113 also has the function of sealing the gap between the positive electrode can 111 and the negative electrode can 112 and blocking the inside and outside of the housing 11 in an airtight and liquid-tight manner.

[0164] The button-type battery 10 is manufactured as follows: First, 52.5 mg of the obtained positive electrode active material, 15 mg of acetylene black and 7.5 mg of polytetrafluoroethylene (PTFE) resin are mixed and granulated into a particle having a diameter of 11 mm and a weight of about 75 mg to manufacture a positive electrode 121, which is then dried in a vacuum dryer at 100° C. for 12 hours.

[0165] The positive electrode 121 , the negative electrode 123 , the separator 122 , and the electrolyte were used to produce the coin-type battery 10 in a glove box of an Ar atmosphere whose dew point was controlled at −60° C.

[0166] As the negative electrode 123 , lithium metal punched into a disk shape with a diameter of 13 mm was used.

[0167] As the separator 122 , a polyethylene porous film having a thickness of 25 μm was used.

[0168] As the electrolyte, a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 (manufactured by Toyama Pharmaceutical Industry Co., Ltd.) using 1 M LiClO 4 as a supporting electrolyte was used.

[0169] [Evaluation of positive electrode active materials and secondary batteries]

[0170] (1) Evaluation of positive electrode active materials

[0171] The produced positive electrode active material was evaluated as follows.

[0172] (a) Average pore size

[0173] The average pore size (unit: μm) of the positive electrode active material was measured using a mercury porosimeter (fully automatic pore distribution measuring device POREMASTER-60-GT). As the average pore size, the average pore diameter was measured.

[0174] The average pore diameter (unit: μm) of the positive electrode active material in the range of 0.0036 μm to 400 μm and the average pore diameter (unit: μm) in the range of 0.0036 μm to 0.5 μm were measured. The cumulative specific surface area and the cumulative pore volume were also measured within the range of the average particle size.

[0175] (b) Cumulative specific surface area

[0176] The cumulative specific surface areas S1 and S2 (unit: m 2 / g).

[0177] (c) Cumulative pore volume

[0178] The cumulative pore volume (unit: cc / g) of the lithium composite oxide particles was measured using a fully automatic pore size distribution measuring apparatus (mercury porosimeter (PoreMaster 60-GT, manufactured by Quantachrome)).

[0179] (d) Proportion of micropores

[0180] Based on the following formula (1), the ratio S2 / S1 of the cumulative specific surface area S2 to the cumulative specific surface area S1 was determined as the ratio of the micropores.

[0181] Micropore ratio (%) = (cumulative specific surface area S2 in the range of pore diameters of 0.0036 μm to 0.5 μm) / (cumulative specific surface area S1 in the range of pore diameters of 0.0036 μm to 400 μm) × 100 (1)

[0182] The evaluation results are shown in Tables 1 and 2. In addition, Table 1 shows the various measurement results when the pore diameter of the pores formed in the positive electrode active material is measured in the range of 0.0036 μm to 400 μm. Table 2 shows the various measurement results when the pore diameter of the pores formed in the positive electrode active material is measured in the range of 0.0036 μm to 0.5 μm and the results of the ratio of micropores.

[0183] (2) Evaluation of battery characteristics

[0184] Use the produced Figure 1As battery characteristics, the charge capacity, initial discharge capacity, and charge and discharge efficiency of the button-type battery shown were measured and evaluated.

[0185] (a) Charging capacity, initial discharge capacity and charge-discharge efficiency

[0186] The button-type battery was placed for about 12 hours after production. After the open circuit voltage (OCV) stabilized, the current density relative to the positive electrode was set to 0.1 mA / cm 2 , the capacity when charging to the cut-off voltage of 4.3V is set as the charging capacity.

[0187] After charging, the battery was paused for 1 hour, and then discharged to a cutoff voltage of 3.0 V, which was defined as the initial discharge capacity.

[0188] The charge and discharge efficiency was calculated as the ratio of the initial discharge capacity to the charge capacity.

[0189] Table 3 shows the evaluation results of the charge capacity, discharge capacity, and charge and discharge efficiency of the produced button-type batteries.

[0190] <Example 2>

[0191] In Example 1, the crystallization conditions in the crystallization step were changed based on preliminary experiments, and the preparation of the positive electrode active material was changed so that the average pore diameter was 0.306 μm. The same operation as in Example 1 was performed. The average particle size of the nickel composite hydroxide particles is expressed as the median particle size D 50 The BET specific surface area of ​​the positive electrode active material is 1.0 m 2 / g. The evaluation results of the average pore diameter, cumulative specific surface area and cumulative pore volume of the positive electrode active material are shown in Tables 1 and 2. In addition, Table 2 shows the proportion of fine pores. The evaluation results of the battery characteristics (charging capacity, initial discharge capacity and charge and discharge efficiency) of the button-type battery are shown in Table 3.

[0192] <Example 3>

[0193] In Example 1, based on the preliminary test, the crystallization conditions in the crystallization step were changed to a molar ratio of nickel:cobalt:aluminum of 87:5:8, and the preparation of the positive electrode active material was changed so that the average pore diameter was 0.415 μm. The same operation as in Example 1 was performed. The average particle size of the nickel composite hydroxide particles is the median particle size D 50 The BET specific surface area of ​​the positive electrode active material is 1.1 m 2 / g. The evaluation results of the average pore diameter, cumulative specific surface area and cumulative pore volume of the positive electrode active material are shown in Tables 1 and 2. In addition, Table 2 shows the proportion of fine pores. The evaluation results of the battery characteristics (charging capacity, initial discharge capacity and charge and discharge efficiency) of the button-type battery are shown in Table 3.

[0194] <Comparative Example 1>

[0195] In Example 1, the crystallization conditions in the crystallization step were changed based on preliminary experiments, and the preparation of the positive electrode active material was changed so that the average pore diameter was 0.198 μm. The same operation as in Example 1 was performed. The average particle size of the nickel composite hydroxide particles is expressed as the median particle size D 50 The BET specific surface area of ​​the positive electrode active material is about 0.7 m 2 / g. The evaluation results of the average pore diameter, cumulative specific surface area and cumulative pore volume of the positive electrode active material are shown in Tables 1 and 2. In addition, Table 2 shows the proportion of fine pores. The evaluation results of the battery characteristics (charging capacity, initial discharge capacity and charge and discharge efficiency) of the button-type battery are shown in Table 3.

[0196] <Comparative Example 2>

[0197] In Example 1, the crystallization conditions in the crystallization step were changed based on preliminary experiments, and the preparation of the positive electrode active material was changed so that the average pore diameter was 0.127 μm. The same operation as in Example 1 was performed. The average particle size of the nickel composite hydroxide particles is expressed as the median particle size D 50 The BET specific surface area of ​​the positive electrode active material is about 0.8 m 2 / g. The evaluation results of the average pore diameter, cumulative specific surface area and cumulative pore volume of the positive electrode active material are shown in Tables 1 and 2. In addition, Table 2 shows the proportion of fine pores. The evaluation results of the battery characteristics (charging capacity, initial discharge capacity and charge and discharge efficiency) of the button-type battery are shown in Table 3.

[0198] <Comparative Example 3>

[0199] In Example 3, the crystallization conditions in the crystallization step were changed based on preliminary experiments, and the preparation of the positive electrode active material was changed so that the average pore diameter was 0.168 μm. The same operation as in Example 3 was performed. The average particle size of the nickel composite hydroxide particles is expressed as the median particle size D 50 The BET specific surface area of ​​the positive electrode active material is about 0.8 m 2 / g. The evaluation results of the average pore diameter, cumulative specific surface area and cumulative pore volume of the positive electrode active material are shown in Tables 1 and 2. In addition, Table 2 shows the proportion of fine pores. The evaluation results of the battery characteristics (charging capacity, initial discharge capacity and charge and discharge efficiency) of the button-type battery are shown in Table 3.

[0200] [Table 1]

[0201]

[0202] [Table 2]

[0203]

[0204] [Table 3]

[0205]

[0206] As shown in Tables 1 and 2, the average pore diameter of the positive electrode active materials of Examples 1 to 3 is 0.306 μm to 0.530 μm when measured in the range of pore diameter 0.0036 μm to 400 μm. As shown in Table 3, the charge and discharge efficiency of the lithium ion secondary battery produced using any positive electrode active material is 89.5% or more.

[0207] On the other hand, it can be seen from Tables 1 and 2 that the average pore diameter of the positive electrode active materials of Comparative Examples 1 to 3 is less than 0.2 μm when measured in the range of pore diameter 0.0036 μm to 400 μm. It can be seen from Table 3 that the charge and discharge efficiency of the lithium ion secondary battery made using any positive electrode active material is about 88.5% or less.

[0208] In addition, it can be seen from Table 3 that when Examples 1 and 2 having the same composition are compared with Comparative Examples 1 and 2, respectively, Examples 1 and 2 have larger initial discharge capacity and charge capacity than Comparative Examples 1 and 2. Similarly, when Example 3 having the same composition is compared with Comparative Example 3, Example 3 has larger initial discharge capacity and charge capacity than Comparative Example 3.

[0209] Therefore, if the average pore diameter when measured within the range of 0.0036μm to 400μm of the pore diameter of the positive electrode active material is 0.306μm to 0.530μm, it can be confirmed that the charge capacity, initial discharge capacity and charge and discharge efficiency of the lithium ion secondary battery can be increased, and the battery characteristics of the lithium ion secondary battery can be improved.

[0210] In addition, it can be seen from Table 2 that in the positive electrode active materials of Examples 1 to 3, the cumulative specific surface area ratio S2 / S1 is 91% or less. On the other hand, in the positive electrode active materials of Comparative Examples 1 to 3, the cumulative specific surface area ratio S2 / S1 is 93% or more. Therefore, it can be said that if the cumulative specific surface area ratio S2 / S1 of the positive electrode active material is 91% or less, the battery characteristics of the lithium ion secondary battery can be improved.

[0211] This application claims priority based on Japanese Patent Application No. 2019-168510 filed with the Japan Patent Office on September 17, 2019, and the entire contents of Japanese Patent Application No. 2019-168510 are incorporated herein by reference.

[0212] Explanation of symbols

[0213] 10 Button type battery

[0214] 11 Housing

[0215] 12 Electrodes

[0216] 121 Positive electrode

[0217] 122 Diaphragm

[0218] 123 Negative electrode

Claims

1. A positive electrode active material for a lithium ion secondary battery, wherein the average pore diameter when measured within a range of pore diameters of 0.0036 μm to 400 μm is 0.2 μm to 1.0 μm, When the ratio S2 / S1 of the cumulative specific surface area S2 measured in the range of pore diameters of 0.0036 μm to 0.5 μm to the cumulative specific surface area S1 measured in the range of pore diameters of 0.0036 μm to 400 μm is defined as the ratio of micropores, The proportion of the micropores is 70% to 92%. The pore diameter is measured using a fully automatic pore diameter distribution measuring device. The cumulative specific surface area is measured using a flow-type gas adsorption method specific surface area measuring device.

2. A lithium ion secondary battery comprising the positive electrode active material for a lithium ion secondary battery according to claim 1.

Citation Information

Patent Citations

  • Non-aqueous electrolyte battery

    JP2002203552A

  • Optical connector cleaning tool

    JP2019168510A

  • Positive electrode material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2015069822A

  • Electrode, non-aqueous electrolyte battery, and battery pack

    WO2019069402A1